Aggressive angiomyxoma of renal pelvis in a horseshoe-shaped kidney: Rare tumor at an unusual site - Nishant Sagar; Prerna Arora; Nita Khurana; P N Agarwal (Wolters Kluwer Medknow Publications, 2020)
Mesenchymal neoplasm is rare in renal pelvic region. Aggressive angiomyxomas are the neoplasms seen predominantly in female genital region. These tumors are locally aggressive with rare cases presenting with metastasis. Its occurrence in renal pelvis is extremely rare with only five cases reported in the literature. The present case is the sixth case reported in a 15-year-old girl who presented to the surgery department as a case of horseshoe kidney. The mass was excised and a diagnosis of aggressive angiomyxoma was rendered.